MENINGKATKAN HASIL BELAJAR SISWA DALAM KETERAMPILAN MENULIS TEKS ARGUMENTASI PADA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA VIDEO ANIMASI - Cahya Dewi; Yeni Sulaeman; Rifki Arif Nugraha; Usep Saepul Mustakim (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This study aims to improve student learning outcomes in argumentation text writing skills by using animated video media. The method used is classroom action research (PTK) conducted in two cycles, each cycle has two meetings, with a research model consisting of four stages, namely planning, action, observation and reflection. The subjects in this study were all fourth grade students of SDN Cikoneng 2, totaling 15 students, consisting of 8 girls and 7 boys with the school year 2023/2024. The data collection techniques used were observation sheets and essay questions. Based on the results of the study that the pre-cycle results had an average of 47 with a percentage of 20%, while cycle I only obtained an average of 61.66 with a percentage of 46%, the results in cycle II could meet the classical requirements of a class with an average of 75.33 and a percentage of 86%. The results of the study that the use of animated video learning media can improve student learning outcomes in argumentation text writing skills in Indonesian language lessons in class IV SDN Cikoneng 2.